Phylogeny‐based conservation priorities for Australian freshwater fishes. Issue 2 (29th September 2021) - Tims, Amy R.; Alroy, John
Abstract: Conservation scientists are increasingly interested in the question of how extinction prunes the tree of life. This question is particularly important for Australian freshwater fishes because there is a broad mix of ∼300 old and young species, many of which are severely threatened. We used a complete species‐level phylogeny of Australian freshwater fishes to examine phylogenetic nonrandomness of extinction risk. We computed the potential loss of phylogenetic diversity by simulating extinction across the tree under a pattern weighted based on International Union for Conservation of Nature extinction risk category and compared this loss to projected diversity loss under a random null model of extinction. Finally, we calculated EDGE (evolutionary distinctiveness, global endangerment) scores for 251 freshwater and 60 brackish species and compiled a list of high‐priority species for conservation actions based on their extinction risk and evolutionary uniqueness. Extinction risk was not random and was clustered in both diversity cradles (recently diversifying, species‐rich clades, such as Galaxiidae and Percichthyidae) and museums (older, species‐poor groups, such as freshwater chondrichthyans). Clustered extinction made little difference to the average expected loss of phylogenetic diversity. However, the upper bound of loss was higher under a selective model of extinction, particularly when the counts of species lost were low. Thus, the loss of highly threatened species would diminish the tree of life more than a null model of randomly distributed extinction. High priority species included both widely recognized and charismatic ones, such as the Queensland lungfish ( Neoceratodus forsteri ), river sharks, and freshwater sawfishes, and lesser‐known species that receive less public attention, including the salamanderfish ( Lepidogalaxias salamandroides ), cave gudgeons, and many galaxiids, rainbowfishes, and pygmy perches. Abstract : Article Impact Statement : Observed patterns of extinction risk imply high phylogenetic diversity loss if insufficient conservation measures are implemented. Abstract : Prioridades de Conservación Basadas en la Filogenia para Peces de Agua Dulce de Australia Resumen: Los científicos de la conservación cada vez están más interesados en el tema de cómo la extinción poda al árbol de la vida. Esta cuestión es particularmente importante para los peces de agua dulce de Australia ya que existe una mezcla amplia de ∼300 especies antiguas y recientes, muchas de las cuales se encuentran seriamente amenazadas. Usamos una filogenia completa a nivel de especie de los peces de agua dulce de Australia para examinar la no aleatoriedad filogenética del riesgo de extinción. Computamos la pérdida potencial de la diversidad filogenética mediante la simulación de la extinción en todo el árbol bajo un patrón ponderado con base en la categoría de riesgo de extinción de la Unión Internacional para la Conservación de la Naturaleza y la comparamos con la pérdida proyectada de diversidad bajo un modelo aleatorio nulo de la extinción. Por último, calculamos los puntajes EDGE (peculiaridad evolutiva, riesgo global) para 251 especies de agua dulce y 60 especies de agua salobre y recopilamos una lista de especies de alta prioridad para las acciones de conservación basada en su riesgo de extinción y su singularidad evolutiva. El riesgo de extinción no fue aleatorio y estuvo agrupado tanto en cunas de diversidad (clados ricos en especies con diversificación reciente, como Galaxiidae y Percichthyidae) como en museos (grupos más viejos con pocas especies, como los condrictios de agua dulce). La extinción agrupada no trajo grandes diferencias para la pérdida promedio esperada de la diversidad filogenética. Sin embargo, el límite superior de la pérdida fue más alto bajo un modelo selectivo de extinción, particularmente cuando los conteos de especies perdidas fueron bajos. Por lo tanto, la pérdida de especies en grave peligro de extinción disminuiría el árbol de la vida más que un modelo nulo de extinción distribuida aleatoriamente. Las especies de mayor prioridad incluyeron tanto a las más conocidas y carismáticas, como el pez pulmonado de Queensland ( Neoceratodus forsteri ), los tiburones de río y los peces sierra de agua dulce, como a las especies menos conocidas que reciben menos atención del público, incluyendo al pez salamandra ( Lepidogalaxias salamandroides ), los gobios de las cuevas y a muchos galaxiidos, peces arcoiris y percas pigmeas.